ANALISIS KINERJA KEUANGAN BADAN AMIL ZAKAT BERDASARKAN PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NOMOR 109 DI KABUPATEN GOWA - Cahyadi, Rahadian (Universitas Muhammadiyah Makassar, 2020)
This research was conducted with the aim to study and analyze the Amil Zakat Agency to be mandatory and responsible in carrying out its functions and duties in terms of the most important work of grouping and financial reporting and where targets are given to people who need help in terms of Zakat, Infak and Sadaqah are therefore very helpful in terms of the community's economy and what the Amil Zakat Agency does in terms of financial reporting is based on financial accounting standards using financial ratio analysis. The results of the proposed research are not yet the maximum application of PSAK number 109 in terms of performance and financial reporting.Keywords: Financial Ratios and PSAK 109